“TAP” technique on bifurcation lesion of Y graft in a patient with NSTEMI complicated with cardiogenic shock - Čanković Milenko (Serbian Medical Society, 2021)
Introduction. Bifurcation lesions on venous Y grafts are rare. We present a case of a woman who developed non-ST segment elevation myocardial infarction complicated by cardiogenic shock due to a bifurcation lesion on the venous Y graft for left anterior descending artery (LAD) and ramus circumflex artery (RCX). Case outline. A 72-year-old woman was admitted to the coronary care unit as an emergency in September 2017 due to acute heart failure followed by the development of cardiogenic shock. Urgent coronarography revealed severe atherosclerotic disease of native coronary arteries with significant bifurcation lesion on venous Y graft for LAD and RCX (medina classification of 1,1,1) with thrombolysis in myocardial infarction (TIMI) grade 2 flow. According to the general condition of patient, a life-saving ad hoc percutaneous coronary intervention (PCI) was performed. Two stents were implanted in the Y graft with T and protrusion (TAP) technique achieving optimal result followed with patient stabilization. On one-year follow-up, the patient was without symptoms of angina, and computed tomography coronarography revealed patent both stents in the Y graft. To the best of our knowledge, this is the first described TAP technique used on the Y graft. Conclusion. The PCI on a vein graft is not uncommon either in elective cases or in cases with acute coronary syndrome due to the poorer persistence and more frequent progression of atherosclerotic disease in the venous grafts. The use of bifurcation techniques for the treatment of lesions on a vein graft and especially on the Y graft is rare, but it can be used the same way it is used in native vessels.